1993
DOI: 10.1002/eji.1830230813
|View full text |Cite
|
Sign up to set email alerts
|

Thymus‐derived cytokine(s) including interleukin‐7 induce increase of T cell receptor α/β+ CD4CD8 T cells which are extrathymically differentiated in athymic nude mice

Abstract: Extrathymic T cell differentiation pathways have been reported, although the thymus is the main site of T cell differentiation. The thymus is also known to produce several cytokines that induce proliferation of thymocytes. In the present study, we investigated the influence of thymus-derived cytokines on extrathymic T cell differentiation by intraperitoneal implantation with a diffusion chamber which encloses fetal thymus (we named it fetal thymus-enclosed diffusion chamber, FTEDC) in athymic BALB/c nu/nu mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Similarly, other groups have reported that IL-7 knockout and IL-7R knockout mice show distinct declines in absolute numbers of thymocytes and IEL 23. Kanai et al 39 found that anti-IL-7 antibody treatment disturbed the induction of αβ-TCR+ T-cells after athymic nude mice were implanted with fetal thymocytes. In our present study, intestinal EC specific over-expression of IL-7 resulted in a significant increase in the total number of IEL, and significant changes in IEL phenotype and increases in the level of IEL proliferation.…”
Section: Discussionmentioning
confidence: 76%
“…Similarly, other groups have reported that IL-7 knockout and IL-7R knockout mice show distinct declines in absolute numbers of thymocytes and IEL 23. Kanai et al 39 found that anti-IL-7 antibody treatment disturbed the induction of αβ-TCR+ T-cells after athymic nude mice were implanted with fetal thymocytes. In our present study, intestinal EC specific over-expression of IL-7 resulted in a significant increase in the total number of IEL, and significant changes in IEL phenotype and increases in the level of IEL proliferation.…”
Section: Discussionmentioning
confidence: 76%
“…The thymus could also act through the production of soluble factors, such as IL-7. It has been shown that implantation of a thymic stroma within a cell-impermeable chamber can increase some T cell populations in nude mice (22). Alternatively, immature precursors may reach not only the gut epithelium but also the thymus, in which they might expand, then migrate and complete their differentiation in the gut wall.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we have previously demonstrated that the IEL of nude and NTX mice have far larger numbers of CD3-IEL than their euthymic counterparts early in ontogeny [ll]. The concept that the thymus can influence differentiation or development of extrathymically derived T cells is not without merit [27,28]. Although some recent reports suggest that some CD3-IEL develop into CD3+ IEL extrathymically [29,30], this has not been definitely established.…”
Section: Discussionmentioning
confidence: 99%